Question 13.3: Simplification of Logical Expression Using the rules of Tabl...
Simplification of Logical Expression
Using the rules of Table 13.11,
Table 13.11 Rules of Boolean algebra
-
- 0+X=X
- 1+X=1
- X+X=X
- X+\overline{X}=1
- 0 \cdot X=0
- 1 \cdot X=X
- X \cdot X=X
- X \cdot \overline{X}=0
- \overline{\overline{X}}=X
- X+Y=Y+X Commutative law
- X \cdot Y=Y \cdot X Commutative law
- X+(Y+Z)=(X+Y)+Z Associative law
- X \cdot(Y \cdot Z)=(X \cdot Y) \cdot Z Associative law
- X \cdot(Y+Z)=X \cdot Y+X \cdot Z Distributive law
- X+X \cdot Z=X Absorption law
- X \cdot(X+Y)=X
- (X+Y) \cdot(X+Z)=X+Y \cdot Z
- X+\overline{X} \cdot Y=X+Y
- X \cdot Y+Y \cdot Z+\overline{X} \cdot Z=X \cdot Y+\overline{X} \cdot Z
simplify the following function using the rules of Boolean algebra.
f(A, B, C, D)=\bar{A} \cdot \bar{B} \cdot D+\bar{A} \cdot B \cdot D+B \cdot C \cdot D+A \cdot C \cdot D
Learn more on how we answer questions.
Find: Simplified expression for logical function of four variables.
Analysis:
\begin{aligned}f &=\bar{A} \cdot \bar{B} \cdot D+\bar{A} \cdot B \cdot D+B \cdot C \cdot D+A \cdot C \cdot D & \\&=\bar{A} \cdot D \cdot(\bar{B}+B)+B \cdot C \cdot D+A \cdot C \cdot D & & \text { Rule } 14 \\&=\bar{A} \cdot D+B \cdot C \cdot D+A \cdot C \cdot D & & \text { Rule } 4 \\&=(\bar{A}+A \cdot C) \cdot D+B \cdot C \cdot D & & \text { Rule } 14 \\&=(\bar{A}+C) \cdot D+B \cdot C \cdot D & & \text { Rule } 18 \\&=\bar{A} \cdot D+C \cdot D+B \cdot C \cdot D & & \text { Rule } 14 \\&=\bar{A} \cdot D+C \cdot D \cdot(1+B) & & \text { Rule } 14 \\&=\bar{A} \cdot D+C \cdot D=(\bar{A}+C) \cdot D & & \text { Rules } 2 \text { and } 6\end{aligned}